Developmentally Delayed Male with Mincer Blade Obstructing the Oesophagus for a Period of Time Suspected to Be 6 Months - Christian Grønhøj Larsen; Birgitte Charabi (Case Reports in Surgery)
Introduction. Sharp, retained foreign bodies in the oesophagus are associated with severe complications. Developmentally delayed patients are especially subject to foreign objects. We describe a 37-year-old, developmentally delayed male with a mincer blade obstructing the oesophagus. Six months prior to surgical intervention, the patient was hospitalized in a condition of sepsis and pneumonia where the thoracic X-ray reveals a foreign body in the proximal oesophagus. When rehospitalized 6 months later, a mincer blade of the type used in immersion blenders was surgically removed. During these 6 months the patient’s main symptoms were dysphagia, weight loss, and diarrhoea. When developmentally delayed patients present with dysphagia, we strongly encourage the awareness of the possible presence of foreign bodies. To our knowledge this is the first reported case of a mincer blade in the oesophagus.